Формування ефективних комунікацій на підприємствах індустрії гостинності як механізм підвищення якості управління персоналом - Каламан, Ольга Борисівна; Каламан, О. Б.; Дишкантюк, Оксана Володимирівна; Дишкантюк, О. В.; Власюк, Каріна Вікторівна; Власюк, К. В. (My University, 2023)
У статті розглянуто особливості комунікаційного процесу на підприємствах індустрії гостинності, запропоновано напрями їх удосконалення, розглянуто структуру комунікаційного процесу та його вузькі місця, бар’єри та проблеми формування ефективних комунікацій на підприємстві. Метаю статті, яка полягала у з’ясуванні та виокремленні особливості формування ефективних комунікацій як механізму підвищення якості управління персоналом саме на підприємствах індустрії гостинності, була досягнута. Завдання статті щодо з’ясування сутності поняття комунікації та комунікаційного процесу, виявлення критеріїв оцінки їх ефективності та надання рекомендацій щодо посилення таких комунікацій для підприємств індустрії гостинності, були виконані. Виокремлено перспективні напрями дослідження, які мають бути зосереджені у аналізі впливу невербальних комунікацій на їхню ефективність з точки зору управління персоналом на підприємствах індустрії гостинності.

The article examines the peculiarities of the communication process in the hospitality industry enterprises, suggests directions for their improvement, considers the structure of the communication process and its bottlenecks, barriers and problems of forming effective communications in the enterprise. It is summarized that communication in the workplace is crucial for establishing and maintaining quality working relationships in organizations as a process of transferring information and common understanding from one person to another. The article proves that effective communication in the workplace is important because every administrative function and activity involves some form of direct or indirect communication. The study shows that in order to increase the effectiveness of communication, including in the hospitality industry, administrators should develop an awareness of the importance of the responsibilities of the sender and the receiver and adhere to active listening skills. The article emphasizes that effective communication skills in the workplace will improve a manager's ability to be a strong leader. It has been found that managers should create an environment in which problems, plans, issues, views, opinions and ideas related to work are discussed and resolved professionally and skillfully through positive and effective communication. The purpose of the article, which was to clarify and highlight the peculiarities of forming effective communications as a mechanism for improving the quality of personnel management in the hospitality industry, has been achieved. The objectives of the article on clarifying the essence of the concept of communication and communication process, identifying criteria for assessing their effectiveness and providing recommendations for strengthening such communications for hospitality industry enterprises have been fulfilled. Promising areas of research that should be focused on analyzing the impact of non-verbal communications on their effectiveness in terms of personnel management in the hospitality industry have been allocated.
Каламан О. Б. Формування ефективних комунікацій на підприємствах індустрії гостинності як механізм підвищення якості управління персоналом / О. Б. Каламан О. В. Дишкантюк, К. В. Власюк // Інфраструктура ринку. - 2023, № 70. - С. 100-106. DOI: https://doi.org/10.32782/infrastruct70-18
Keywords: комунікацій; комунікативний процес; менеджмент; управління персоналом; підприємства індустрії гостинності; ефективні комунікації; communications; communication process; management; personnel management; hospitality industry enterprises; effective communications; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Domestic science and nutrition